Pembuktian Unsur Kesengajaan dalam Tindak Pidana Pembunuhan Berdasarkan Pasal 338 KUHP : (Studi Putusan No 122/Pid.B/2021/PN.Sit) - Hindriyani Hindriyani; Heriyanto Heriyanto (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
The crime of murder is a crime that can cause the death of a person, this is committed individually and violates the applicable provisions of the Criminal Code Book II Chapter XIX (articles 338-350). Basically, murder is carried out with an element of intent. Deliberation is a subjective element in a criminal act, because this element is inherent in the subject or perpetrator of the crime. This means wanting or knowing what will be done. Therefore, in murder there must be evidence in order to determine whether a person is guilty or not in committing the crime of murder by collecting legal evidence according to the applicable law. Furthermore, the method used in this case is a normative juridical approach, which is carried out through literature books, journals, articles, as well as statutory regulations related to the problem to be discussed. Legal considerations in imposing a sentence on the perpetrator of the crime of intentional murder, because the circumstances were aggravating and the defendant caused the victim to die and the defendant's actions disturbed the community. Thus, the punishment given by the state is solely to change the perpetrator to become better, and at the same time provide education to improve themselves.